A FRAMEWORK FOR FATIGUE ASSESSMENT OF STEEL TRUSS BRIDGES - AYILARA, AJIBOLA QUADRI (2016)
The perpetual chase for economic growth through industrialisation of urban cities demands continuous movement of people, raw materials and finished goods. For the carriage of raw materials and finished goods, the final stage of transportation is often through highways using heavy goods vehicles. Malaysia being a growing economy with speedy industrialisation is faced with a surge in vehicular traffic. With the rise in population of heavy goods vehicles and traffic volume, enforcement of legal load limits has become more arduous for monitoring agencies. Thus, it is rampant for heavy goods vehicle to be overloaded in both the Peninsula and East Malaysia, with vehicles reported to be overloaded by up to 100% of their maximum allowable GVW.